Continent Idiopathic Vesicovaginal Fistula Coexisting with Moyamoya Disease - İbrahim Güven Kartal; Mehmet Ezer; Tahsin Batuhan Aydoğan; Ali Ergen (Journal of Urological Surgery)
Vesicovaginal fistula (VVF) is the abnormal anatomic communication between the female bladder and vagina. Usually presents itself as continuous urinary incontinence. There are many etiologic risk factors such as obstetric trauma, pelvic surgery, infections, congenital abnormalities, foreign materials, malignancy and pelvic radiation (1). Due to high education and sociocultural levels, the incidence seems to be low in the developed countries. On the other hand, in the developing countries, there is an obviously high incidence and prevalence. Considering the low level of medical informative feed-back mechanisms and poor obstetrics health care services, it seems very hard to keep VVF patient data that can be used for epidemiological research studies. In those areas, due to high maternal mortality and obstetric complications, the incidence of VVF is significantly increased (2). In this paper, we report a female patient with known moyamoya disease and a stable right ovarian cyst who was regularly followed up by the departments of neurology, gynecology and presented with radiological and cystoscopy findings of incidentally diagnosed asymptomatic continent VVF.